DAMP AI( HAMBATAN NON-TARIF TERHADAP PERMINT AAN EKSPOR UDANG INDONESIA KE UNI EROPA - Toni Kuswoyo; Dwidjono Hadi Darwanto; Slamet Hartono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2007)
This research was aimed to determine theforms of the non-tarifbarrier and its impact to the Indonesian shrimp export demand to the European Union (EU), beside the other factors as constructor of demand function. This research used secondary data (lime series) during 23 years (1984-2006): shrimp export volume (Qd), shrimp export price (Px), domestic shrimp price (Pd), crab export price (Pk), exchange rate from the importing countries, and commerce regulations which is peiformed by EU as dummy variables. The data collected from DKP, BPS, Depdag, internet, and other relevant institutions. Peculiarly, the dummy variable grouped into 6 groups: RASFF (DI), contaminant (D2), certain substances & residues (D3), health conditions & food hVf!iene rules (D4), HCCP (D5), and marketinf! standards (D6).This research used the multiple regression analysis model, with the tolerant time (!gg) I year from tfor several dummy variables. Analysis were conducted at 6 markets: UE as a whole, Dutch, United Kingdom (UK), French, Germany, and Belgia and Luxemburg. Testing of the classical assumptions conducted by the econometric criterions is covering the economic and statistic criterions. The estimation of the regression parameters conducted by the smallest square method (ordinarv least SQuare. OLS) and model repaired as the effect of existence of the first order autocorrelation by a comand